Convergence Model of Skill India Mission – 2009-2017: A Review: Analyzing the Convergence Model of Skill India Mission and its Impact (Journal of Advances and Scholarly Researches in Allied Education, 2017)
“Today the world focuses on trade in goods but in future the core issue will be how to get skilled people. We need to work in this direction” – Prime Minister of India, Shri Narendra Modi, July 2014.